2015
DOI: 10.15639/teflinjournal.v26i1/117-128
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Pre-Service Teachers’ Classroom Management Skills Through Teaching Practicum: A Reflective Practice

Abstract: Classroom management is commonly believed to be the key to the success of an instruction. Many student teachers, however, might find it very challenging to handle their classrooms. It is, therefore, necessary to advance their professional practice in the context of a real classroom such as through teaching practicum and reflective practice. This study is aimed at identifying classroom management problems of student-teachers as revealed in their reflective journal entries and to demonstrate how such journal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
3
13
0
Order By: Relevance
“…The in-service teachers tended to use more types of strategies to begin and end lessons, more variety of tools and techniques and in a more versatile and flexible way. Similar findings were found in other studies such as Reupert and Woodcock (2010); Ünal and Ünal (2012);and Ragawanti (2015). These differences can be explained by the stages of teacher development theories (Wright, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The in-service teachers tended to use more types of strategies to begin and end lessons, more variety of tools and techniques and in a more versatile and flexible way. Similar findings were found in other studies such as Reupert and Woodcock (2010); Ünal and Ünal (2012);and Ragawanti (2015). These differences can be explained by the stages of teacher development theories (Wright, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…For example, Ragawanti (2015) identified the classroom management problems of student teachers through their reflective journals. Using Scrievener's (2005) classification of classroom management, he found that the most problematic area was managing critical moments, especially in terms of maintaining the silence and controlling the noise level.…”
Section: Classroom Managementmentioning
confidence: 99%
“…The research focus mostly concerns with classroom issues, teacher identity, and beliefs in teaching (see, Astika, 2014;Cahyono, 2014;Kuswandono, 2014;Palupi, 2011;Ragawanti, 2015), while there is still scarcity of empirical studies investigating the level of reflection of EFL pre-service teachers (see Nurlaelawati, 2015) in Indonesian classroom contexts. Identifying levels of reflection is deemed to be of paramount because it justifies the quality of the teachers' reflection (Hatton & Smith, 1995;Ulusoy, 2016).…”
mentioning
confidence: 99%
“…Regardless of these intricate power relations in which Diva was socioculturally situated, her telling somehow constructed a positive image of her as a person who was capable of managing her class, particularly with her debating skill. It is often the case that classroom management is one of the most challenging skills for novice teachers, especially in handling students' noise (Ragawanti, 2015). However, a narrative analysis of Diva's story provides a better outlook of how a novice/student-teacher managed her class through her sense of agency as a debater.…”
Section: Resultsmentioning
confidence: 99%
“…Though not observed using a narrative inquiry framework, recent studies (e.g., Anindra, 2016;Ragawanti, 2015) have taken up themes of studentteachers' concerns during teaching practicum which they have documented in their teaching reflections. Some major concerns are related to teaching methods (including classroom management issues), personal problems, lesson planning, and communication problems.…”
Section: Teaching Practicum Experiencesmentioning
confidence: 99%